2013
DOI: 10.15171/ijhpm.2013.04
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Policy Making: Clinical Appropriateness Study of Lumbar Spine MRI Prescriptions Using RAND Appropriateness Method

Abstract: In conclusion, a large proportion of lumbar spine MRI prescriptions, which result in financial burden on the insurance companies and the patients alike is unnecessary. This study suggests that policy makers consider this evidence while decision-making. Our findings highlight the imperative role of Health Technology Assessment (HTA) and Clinical Practice Guidelines (CPGs). As a result, developing local clinical guidelines may create the commitment needed in physicians in prescribing appropriate prescriptions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…In addition, 38.8% of inappropriate prescription costs were paid by insurance organizations and 61.2% was paid by patients. Salari et al reported that the estimated economic burden of 167 inappropriate prescriptions was $2095, and Sadeghi et al found that the monthly cost of unnecessary MRIs was $6643. Diagnostic imaging and clinical intervention for back pain impose a considerable economic burden on the health care systems of many countries, and the increased use of advanced imaging procedures such as MRI has also increased concerted recent attempts at cost reduction .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 38.8% of inappropriate prescription costs were paid by insurance organizations and 61.2% was paid by patients. Salari et al reported that the estimated economic burden of 167 inappropriate prescriptions was $2095, and Sadeghi et al found that the monthly cost of unnecessary MRIs was $6643. Diagnostic imaging and clinical intervention for back pain impose a considerable economic burden on the health care systems of many countries, and the increased use of advanced imaging procedures such as MRI has also increased concerted recent attempts at cost reduction .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the patient share of costs can be increased to improve the efficiency and effectiveness of the services. This intervention could reduce the ethical hazards and requests made by individuals having supplementary insurance because of the additional cost . It is possible for insurance organizations to reduce their economic burden and that of patients by providing training and departments that supervise physician prescriptions in accordance with clinical guidelines …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They calculated the costs of inappropriate prescriptions to be 88009000 IRR. 10 Ebrahimipour and et al studied the appropriateness of knee MRI examinations in Mashhad and found that 54.8% were inappropriate, 14.8% were uncertain and 30.4% were appropriate with the cost of 38159100 IRR. 8 The huge financial burden imposed on insurance companies and patients shows the importance of using such evidence by policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire consisted of 12 questions related to demographic characteristics and questions related to MRI prescription. The questionnaire validity and reliability were determined by Salari et al 10 The Clinical Guidelines (CGs) developed by Ebrahimipour et al 8 was used to identify prescription appropriateness. The patients' clinical histories were examined by experienced specialists who were involved in the Clinical Guidelines development, so that the prescription appropriateness can be determined in accordance with the guide.…”
Section: Methodsmentioning
confidence: 99%